Chemical composition, antimicrobial and anticancer activities of Paederia lanuginosa WALL - Hiep Hoang Phu; Tran Thi Hong; Van Khang Pham (Biotechnology & Biotechnological Equipment)
Paederia lanuginosa WALL. (P. lanuginosa) is a medicinal herb used to treat leprosy, expel worms, detoxify the body, and address stomach-related illnesses. On the other hand, P. lanuginosa leaves can also be used as a culinary spice. This study investigates the chemical composition of P. lanuginosa leaf extracts prepared with alcohol and it also evaluates the potential of these extracts for various biological activities, including antibacterial, antifungal and anticancer properties. The results showed that the alcoholic extract of P. lanuginosa leaves includes organic compounds such as alkaloids, iridoid glycosides, flavonoid, tannin, anthraquinone, and terpenoid. The extract did not contain saponin, coumarin, steroid, deodorised sugars, or carboxylic acids. The extract exhibited good broad-spectrum antibacterial activity at a concentration of 50 μg/mL against the tested bacterial strains Escherichia coli, Bacillus subtilis, Lactobacillus plantarum, and Helicobacter pylori. Furthermore, the extract displayed good antifungal activity against Aspergillus brasiliensis, Aspergillus flavus, and Candida albicans at a concentration of 50 μg/mL. The extract of P. lanuginosa leaves also showed moderate inhibitory activity against the three tested cancer cell lines MKN-7, SW480, and HT29, with IC50 values ranging from 25.26 to 28.83 µg/mL.